Modern Approaches to Local Treatment of PurulentNecrotic Complications of Diabetic Foot Syndrome - Khudaynazarov Utkir Rabbimovich; Abdullaev Sayfulla Abdullaevich; Yuldoshev Farrukh Shokirovich (Zien Journals, 2022)
Diabetes mellitus is one of the most acute medical and social problems of our time, covering most economically developed countries. According to the forecasts of the International Diabetes Federation, 592 million people will suffer from diabetes by 2035. One of the formidable complications of diabetes mellitus is diabetic foot syndrome, as the treatment of purulent-destructive lesions of the lower extremities requires significant material costs, does not always work effectively and often ends with amputations, which are carried out 17-45 times more often than in the general population, often performing them at the level of the lower leg and hip, which increases postoperative mortality up to 50% and leads to disability of the patient. Epidemiological studies have shown that 6-30% of patients with diabetic foot syndrome with purulent-necrotic complications after the first amputation undergo amputation of the second limb within 1- 3 years, after 5 years – 28-51%. All these data indicate that this problem is unresolved and it is advisable to further develop new tactical approaches to the treatment of this category of patients to reduce the incidence of disability and mortality.
Keywords: diabetes mellitus; diabetic foot syndrome; necrectomy; local treatment